Critical Illness Polyneuropathy: a multicenter study on functional outcome (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
Objective. To describe the functional recovery of consecutive inpatients with Critical Illness Polyneuropathy (CIP) at the time-point of the discharge from rehabilitation units according to Barthel Index scores. To examine whether age, gender, pre-ICU admission diagnosis, tracheostomy performance, heterotopic ossification development and duration of neuro-rehabilitation treatment are among the prognostic factors that can predict the functional outcome in studied patients. Design. A retrospective observational clinical study from January 2010 to December 2014. Three rehabilitation units in Greece. Results. Sixteen subjects (57.1%) had >60 Bl discharge scores, showing a prospect in gaining further independence. Females presented a tendency for better functional outcome vs males (73.8±12.6 vs 58.6±23.4, p=0.082). Respiratory, septic and neurologic patients demonstrated better rates of functional improvement after the rehabilitation process vs cardiac patients (p<0.001, p=0.009 and p=0.019, respectively vs p=0,072). Heterotopic ossification development proved to be an adverse independent prognostic factor of functional outcome (47.8 ≤ 25.7 vs 68.8 ≤ 17.7, p=0.023). Conclusions. A proportion of included patients experienced severe disability with poor prospect of further functional development and return to work at the discharge from the rehabilitation units. According to the present study, which is the first that focuses only on CIP and its outcome, specific prognostic factors can be defined. Our results can be used as pilot data for larger studies, so that firmer conclusions can be drawn.